If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14y + -20y = 0 Combine like terms: -14y + -20y = -34y -34y = 0 Solving -34y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-34'. y = 0 Simplifying y = 0
| 9u-8u=11 | | 30=5[x+1] | | (x+4)+(x+5)+(x+5)=2 | | -16x^2=1 | | 12x-6=12+15x | | 42=7[z-3] | | (x+4)(x+1)(x-(3+i))(x-(3-i))=0 | | 2x^2-1=-163 | | 8y-6y=20 | | 13=9t-14 | | (8x+7)(x+1)=9 | | 16x^2+24ax+8y^2=0 | | 14g-13g=7 | | X*-1=24 | | 2y(y-1)+6y=-10 | | 9/4-3/4= | | F(-3)=3x+7 | | y=6kx-2 | | 9(2+(-14))-4(-14)=3(-14)-10 | | 8x^2+24ax+8y^2=0 | | 15x-9x^2=0 | | 15x-9x^2=0 | | 8x^2+24ax+8y^2=0 | | (14-2x)=(12x+4) | | -50+5x+x^2=48 | | 6-5x=15x-34 | | -6x=-150 | | -8+2-6r-7huser=8 | | 3x^3-25x^2-50x=0 | | 3x^3-25x^2-50x=0 | | 7x-.25=15 | | 20=5-3u |